ISLAM, POLITICS AND SOCIETY IN ASIA-PACIFIC - Sofiandi Sofiandi; Imam Hanafi (Asia-Pacific Journal on Religion and Society, 2022)
This article highlights the phenomenon of Islam and its crucial role in the Asia-Pacific region and its relationship with geopolitics, foreign policy and national and regional security amidst the wave of radicalism that is always associated with Islam. The focus of the study is on three key countries Pakistan, Malaysia and Indonesia, as the countries with the largest Muslim majorities in the world, though there are significant historical and current differences in the role played by Islam, each of these countries is to a greater or lesser extent searching for an accommodation involving organized Islam.